Thinking strategically expert solutions to everyday challenges. - Harvard Business School (Boston, Mass. : Harvard Business Press, 2010)
"To be a successful manager, you need to master the skills that characterize strategic thinking--from examining situations to interpreting information--and know how to apply those skills on the job." "The Pocket Mentor series offers immediate solutions to the challenges managers face on the job every day. Each book in the series is packed with handy tools, self-tests, and real-life examples to help you identify strengths and weaknesses and hone critical skills. Whether you're at your desk, in a meeting, or on the road, these portable guides enable you to tackle the daily demands of your work with greater speed, savvy, and effectiveness."--BOOK JACKET.
Includes bibliographical references (p. 105-106).
Description based on print version record.
Keywords: Strategic planning; Leadership; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books